Plant‐Derived Substances Used Against Beetles–Pests of Stored Crops and Food–and Their Mode of Action: A Review. Issue 5 (26th July 2018) - Spochacz, Marta; Chowański, Szymon; Walkowiak‐Nowicka, Karolina; Szymczak, Monika; Adamski, Zbigniew
Abstract: Plants are sources of numerous active substances that are used to protect crops. Currently, due to the limitations of using synthetic insecticides, plant products have attracted increasing attention as possible pesticides. In this review, we discuss some of the most interesting plant products (for example, Solanaceae, or Asteraceae extracts, Artemisia absinthium or Citrus spp . essential oils, and single compounds like α‐chaconine, or α‐solanine) that exhibit insecticidal activity against beetles that are pests of stored food products. Next, we describe and discuss the mode of action of these products, including lethal and sublethal effects, such as antifeedant or neurotoxic activity, ultrastructural malformation, and effects on prooxidant/antioxidant balance. Furthermore, the methods of application of plant‐derived substances in food storage areas are presented.